Numerical investigation of the impact of Kenenisa Bekele`s cooperative drafting strategy on its running power during the 2019 Berlin marathon - Polidori, G.; Legrand, F.; Bogard, F.; Madaci, F.; Beaumont, F. (Journal of Biomechanics, 2020)
In this paper we examined the aerodynamic drag and the resulting decrease of power output associated with the drafting positions used by Kenenisa Bekele at the 2019 Berlin marathon. Examination of videos of the race revealed three different positions adopted by Bekele directly behind a frontline of three runners. These drafting positions were numerically studied using CFD simulations performed with the RANS equations and the SST k-Omega model. Depending on his position behind the pacers, our analyses indicated that Bekele`s drafting strategy resulted in reductions of 38.5-57.3% of the drag resistance and aerodynamic power. In terms of metabolic power, Bekele`s drafting positions yielded an estimated 1.91-2.84% reduction compared to the calculated metabolic power of 1427.89 W (or equivalent metabolic power relative to body mass of 25.50 W/kg) that Bekele would have developed if he had run alone at the same speed of 5.75 m.s-1.